EFEKTIVITAS STRATEGI KOMUNIKASI PROGRAM SPADA PRO 2 RRI SAMARINDA DALAM MENINGKATKAN PENDENGAR GEN Z - Rani Berliana; Ainun Ni'Matu Rohmah; Silviana Purwanti; Ziya Ibrizah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
SPADA Pro 2 RRI Samarinda is a radio program designed to align radio communication practices with the media consumption habits of Generation Z. This descriptive qualitative study aims to analyze the effectiveness of the SPADA communication strategy and identify the factors that support and hinder its implementation. Research data were collected through in-depth interviews with three informants and analyzed using Cangara’s (2022) communication strategy model and Rogers’ (2003) concept of the change agent. The findings indicate that the SPADA communication strategy was effective during the planning and implementation stages through the use of slang expressions, personal forms of address, and the utilization of interactive Instagram Story features. The role of broadcasters as change agents was also found to reduce the social distance between the institution and its target group. Several challenges were identified, including audience research that relied on intuition rather than independent social mapping, budget-related bureaucratic constraints during the reporting stage, and evaluation practices that focused primarily on responses from loyal listeners. The study also found a mismatch between the program’s formal communication objectives and its casual style of message delivery.